Associations between sulfides, carbonaceous material, gold and other trace elements in polyframboids: Implications for the source of orogenic gold deposits, Otago Schist, New Zealand. (1st May 2016) - Hu, Si-Yu; Evans, Katy; Fisher, Louise; Rempel, Kirsten; Craw, Dave; Evans, Noreen J.; Cumberland, Susan; Robert, Aileen; Grice, Kliti
Abstract: Intimately intergrown micron-scale framboidal pyrite, carbonaceous material (CM), chalcopyrite, sphalerite and cobaltite form polyframboids in prehnite–pumpellyite facies rocks of the Otago Schist, New Zealand. This study quantifies the metal contents of these polyframboids using synchrotron X-ray fluorescence (SXRF) and laser ablation inductively coupled plasma spectrometry (LA-ICP-MS). Trace elements Au, Zn, As, Mo, Co, Ni, Cu, Ag and Pb are significantly enriched in the polyframboids. The distribution of Zn most closely follows that of CM, and was probably absorbed into the structure of the polyframboids during biogenic processes. The concentrations of Au and Ag are positively corrected with the Zn concentration in the polyframboids ( R 2 of Au–Zn and Ag–Zn are 0.81 and 0.89, respectively.). The concentration of other trace elements, such as As, Co and Cu, which occur adjacent to Zn on elemental maps, show a weak relationship with Zn and may have been incorporated into the polyframboids during later processes. These polyframboids are a probable source for gold and other elements in the orogenic gold mineralization system of the Otago Schist. Metamorphic transformation of the polyframboids may have released the metallic elements into the mineralizing fluid during prograde metamorphism of the schist belt.